Social capital and community participation in the sustainable development of Chedi Bucha Canal - Kiaochaoum, Praepattra; Thawornratana, Chutathip; Tanpichai, Prasong (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
This qualitative research aims to study: 1. Social capital appearing in the community along the Chedi Bucha Canal, Nakhon Pathom Province; 2. Relationship of social capital with community participation in the development of the Chedi Bucha Canal; and 3. Guidelines for contributing social capital by implementing community participation in the sustainable development of the Chedi Bucha Canal. The samples were selected using a purposive sampling method, namely community leaders, volunteer leaders, religious leaders, community scholars and local academics, totaling 14 samples. The instruments comprised of a documentary analysis form, focus group discussion, and group discussion guideline. Data were collected using in-depth interviews. Methods for examining triangular data include 1) data, 2) data collection, 3) a summary creation and confirmation of the conclusion. Data were analyzed using content analysis and thematic analysis. The research results found that: 1. Social capital that appears in the community along Chedi Bucha Canal, Nakhon Pathom Province included 1) human capital 2) institutional capital 3) wisdom and cultural capital, and 4) natural resource capital. 2. The relationship of social capital with community participation in the development of Chedi Bucha Canal included 1) Cultural heritage, 2) Shared consciousness, 3) Network relationships, 4) Potential of people in the community, and 5) Potential of community leaders. 3. Guidelines for contributing social capital by implementing community participation in the development of Chedi Bucha Canal to strengthen and sustain consisted of 1) Promoting community participation, 2) Developing community leaders, 3) Creating collaborative networks, 4) Promoting community knowledge and skills, 5) Raising funds and resources, and 6) Continuously evaluating and improving the Chedi Bucha Canal Development Project.